Electronic properties of atomic layer deposition films, anatase and rutile TiO2 studied by resonant photoemission spectroscopy. (7th June 2016) - Das, C; Richter, M; Tallarida, M; Schmeisser, D
Abstract: The TiO2 films are prepared by atomic layer deposition (ALD) method using titanium isopropoxide precursors at 250 °C and analyzed using resonant photoemission spectroscopy (resPES). We report on the Ti2p and O1s core levels, on the valence band (VB) spectra and x-ray absorption spectroscopy (XAS) data, and on the resonant photoelectron spectroscopy (resPES) profiles at the O1s and the Ti3p absorption edges. We determine the elemental abundance, the position of the VB maxima, the partial density of states (PDOS) in the VB and in the conduction band (CB) and collect these data in a band scheme. In addition, we analyze the band-gap states as well as the intrinsic states due to polarons and charge-transfer excitations. These states are found to cause multiple Auger decay processes upon resonant excitation. We identify several of these processes and determine their relative contribution to the Auger signal quantitatively. As our resPES data allow a quantitative analysis of these defect states, we determine the relative abundance of the PDOS in the VB and in CB and also the charge neutrality level. The anatase and rutile polymorphs of TiO2 are analyzed in the same way as the TiO2 ALD layer. The electronic properties of the TiO2 ALD layer are compared with the anatase and rutile polymorphs of TiO2 . In our comparative study, we find that ALD has its own characteristic electronic structure that is distinct from that of anatase and rutile. However, many details of the electronic structure are comparable and we benefit from our spectroscopic data and our careful analysis to find these differences. These can be attributed to a stronger hybridization of the O2p and Ti3d4s states for the ALD films when compared to the anatase and rutile polymorphs.